Caminhos e travessias do desenho infantil: experiências de infância e formação que emergem na narrativa de si de professoras da educação infantil - Andrade, Ana Caroline Sales (2022)
This work has as general objective to investigate the relationship, in the practice of drawing, between the childhood experiences and formation of Early Childhood Education teachers from the municipality of Fortaleza, starting from their life narratives. As specific objectives, it seeks to identify the manifestation of children’s drawing in the life narratives of these teachers; understand how childhood experiences related to drawing manifest themselves in the life narrative of these teachers; and know formation experiences that underlie the pedagogical practice of the investigated teachers. To answer these objectives, we propose a discussion bringing together the following themes: drawing as an expressive language for children and the place of children’s drawing in school, based on studies by Derdyk (2015), Albano (2013) among other authors; childhood as an experience, based on the Philosophy of Education, from the studies by Kohan (2007), Larrosa (2015), Castro (2013) and Frota (2007); and the theoretical-methodological scope around (auto)biographical research, within the universe of qualitative research in education, based on studies by Delory-Momberger (2008), Passeggi (2008) and Ferrarotti (2010). The research data were constructed through narrative interviews with teachers of Early Childhood Education from the Municipal Education Network of Fortaleza. From these narratives, it was possible to recognize how the drawing appeared in their childhood. At school, drawing was understood as painting ready-made drawings; in the games, the drawing was presented in a creative way, so that the teachers found ways to experience this language with the materials and spaces to which they had access. It was also possible to find, from the teachers’ narratives, gaps in the initial formation on the theme of children’s drawing, and it was only in the continuing education that these professionals had access to theories on the subject. It was possible to perceive that, as in childhood, they created spaces for drawing, while adults and teachers they continue to resist the lack of materials and spaces, without ceasing to be critical of the devaluation of drawing in face of languages prioritized at school, such as reading and writing.